SIKAP, KEPUASAN, DAN LOYALITAS KONSUMEN PRODUK OLAHAN BEBEK (KASUS DI RUMAH MAKAN BEBEK BELUR DI BANDAR LAMPUNG) - Yunarni Martha Doloksaribu; Yaktiworo Indriani; Umi Kalsum (Lampung University, 2016)
The aims of this research are to determine the consumers’ pattern on purchasing, attitudes, satisfaction, and loyalty to duck products at Bebek Belur Restaurant. This research was conducted at two purposive location of Bebek Belur Restaurant in Bandar Lampung, at Z.A Pagar Alam Street Gedung Meneng and at Pramuka Street. The samples of this research are 60 peoples who were selected by accidental sampling. Research data was analyzed by descriptive, qualitative, and quantitative Fishbein Multiatribut Model, Consumer Satisfaction Index (CSI), and the loyalty pyramid. The result of this research showed that purchasing patterns consisted of the total spending amounted Rp31,000-Rp50,000 per payment including only one portion of duck, the eating time was at noon (40%), and came to the restaurant alone or accompanied by one person. The consumer attitude score (Ao) of duck products at Bebek Belur Restaurant amounted 16.42. Consumer of duck products were in the satisfied criteria amounted 72.69 percent. Consumers of duck products on the loyalty pyramid were categorized as loyal, because 83.33 percent of them were committed buyer.Key words: attitude, duck products, loyalty, satisfaction